MOTILITY, RECOVERY RATE, AND PLASMA MEMBRANE INTEGRITY OF ONGOLE CROSSBREED BULL SPERMATOZOA AFTER CRYOPRESERVATION WITH THE ADDITION OF VITAMIN C, SODIUM SELENITE, AND THEIR COMBINATION IN SKIM MILK-EGG YOLK EXTENDER - Kadek Dian Krisna Putrik; Asmarani Kusumawati; Erif Maha Nugraha Setyawan (Buletin Veteriner Udayana, 2025)
Ongole crossbred (OC) cattle are an important genetic resource that requires preservation, and one method to support this is gamete cryopreservation. However, the cryopreservation process often results in reduced sperm viability. This study aimed to evaluate the effect of adding sodium selenite, vitamin C, and its combination as antioxidants in the semen extender on post-thaw sperm quality. Semen was collected from five OC bulls aged 7–9 years. The study consisted of several stages: preparation of the extender, semen collection and evaluation, dilution and freezing, thawing, and post-thaw quality assessment. Sperm motility and membrane integrity were measured as quality parameters. Data were analyzed using one-way ANOVA followed by Duncan’s Multiple Range Test (DMRT) with SPSS software. The results showed that supplementation with 1 µg/mL sodium selenite significantly maintained sperm motility (46.00 ± 2.23%), recovery rate (63.05 ± 2.94%), and membrane integrity (62.20 ± 1.92%) compared to the control. The addition of 5 mM vitamin C also preserved sperm quality, with motility (41.00 ± 2.23%), recovery rate (56.18 ± 2.85%), and membrane integrity (56.10 ± 1.81%). However, the combination of 5 mM vitamin C and 1 µg/mL sodium selenite resulted in lower values for motility (35.00 ± 3.53%), recovery rate (48.00 ± 5.36%), and membrane integrity (48.00 ± 2.23%). In conclusion, sodium selenite was more effective than vitamin C in preserving sperm membrane integrity, while the combination of both antioxidants showed a negative effect. Further studies are recommended to evaluate reactive oxygen species (ROS) levels in each treatment and to determine the optimal antioxidant dosage.